PENERAPAN ABSENSI FINGER PRINT UNTUK MENINGKATKAN DISIPLIN KERJA PEGAWAI - Desmarini, Desmarini; Kasman, Rukun (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This study found out the application of fingerprint attendance to improve employee work discipline at SMA 2 Batang Kapas. In this study, we used qualitative descriptive method, illustrates the phenomenon of the application of fingerprint-based attendance to improve employee work discipline at the SMA 2 Batang Kapas School. The results obtained indicate that (1) fingerprint attendance system is very easy to use; (2) the presence of fingerprints can make employees avoid cheating; (3) the application of fingerprint attendance to improve employee work discipline has run quite well although there are still some shortcomings.